NUTRISI DAN BEBERAPA KRITERIA HALAL KERUPUK KULIT JANGEK - Lula Nadia (Jurnal Matematika Sains dan Teknologi, 2005)
The research goal was to find the nutrition content of the skin crackers ‘Kerupuk Jangek’. Several steps were used to determine the traditional production process, the nutrition content, hedonic value, and halal criteria. The research employed survey and laboratory works. Survey was conducted in Jangek area, West Sumatera to gain information on the skin cracker production process and its type industry. Laboratory works were done in IPB for organoleptic testing. Based on the BPOM guidance, the Kerupuk Jangek production process has followed the halal requirement. The beef skin cracker was more crunchy and tasty than the buffalo skin cracker. The crackers contained high level of protein which can not be digested and absorbed by human body. The crackers contained higher level of lipid than the raw. The beef skin crackers contained less mineral and water than the buffalo skin crackers.